2018
DOI: 10.1002/jmr.2768
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structural analysis of fibronectin‐binding protein reveals importance of multiple intrinsic disordered tandem repeats

Abstract: The location of certain amino acid sequences like repeats along the polypeptide chain is very important in the context of forming the overall shape of the protein molecule which in fact determines its function. In gram‐positive bacteria, fibronectin‐binding protein (FnBP) is one such repeat containing protein, and it is a cell wall‐attached protein responsible for various acute infections in human. Several studies on sequence, structure, and function of fibronectin‐binding regions of FnBPs were reported; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…Therefore, it is not surprising that there are several families of protein repeats including: Armadillo repeats [53], Ankyrin repeats [54], HEAT repeats [55], leucine-rich repeats [56], Kelch-like repeats [57], WD40 (also known as WD or β-transducin) repeats [58], Pentatricopeptide repeats [59], and Tetratricopeptide Repeats (TPR). It was shown that many repeat-containing proteins are characterized by high levels of intrinsic disorder, and that many protein tandem repeats can be intrinsically disordered [60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that there are several families of protein repeats including: Armadillo repeats [53], Ankyrin repeats [54], HEAT repeats [55], leucine-rich repeats [56], Kelch-like repeats [57], WD40 (also known as WD or β-transducin) repeats [58], Pentatricopeptide repeats [59], and Tetratricopeptide Repeats (TPR). It was shown that many repeat-containing proteins are characterized by high levels of intrinsic disorder, and that many protein tandem repeats can be intrinsically disordered [60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…characterized by high levels of intrinsic disorder, and that many protein tandem repeats can be intrinsically disordered [60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been documented that the existence of TR in proteins promotes their function as adhesion molecules [ 43 , 44 ], next we have analyzed the presence and frequency of TRs in the 75 Bcc-CLPs (XSTREAM web server [ 35 ]). As shown in Figure 3 , the existence of TR in the majority of the 75 Bcc-CLPs is notable, being absent in only five proteins (6%).…”
Section: Resultsmentioning
confidence: 99%